Anti-C2 Antibody ARGX-117 Inhibits Complement in a Disease Model for Multifocal Motor Neuropathy. Issue 1 (10th January 2022) - Budding, Kevin; Johansen, Lill Eva; Van de Walle, Inge; Dijkxhoorn, Kim; de Zeeuw, Elisabeth; Bloemenkamp, Lauri M.; Bos, Jeroen W.; Jansen, Marc D.; Curial, Chantall A.D.; Silence, Karen; de Haard, Hans; Blanchetot, Christophe; et al.
Abstract : Background and Objectives: To determine the role of complement in the disease pathology of multifocal motor neuropathy (MMN), we investigated complement activation, and inhibition, on binding of MMN patient-derived immunoglobulin M (IgM) antibodies in an induced pluripotent stem cell (iPSC)-derived motor neuron (MN) model for MMN. Methods: iPSC-derived MNs were characterized for the expression of complement receptors and membrane-bound regulators, for the binding of circulating IgM anti-GM1 from patients with MMN, and for subsequent fixation of C4 and C3 on incubation with fresh serum. The potency of ARGX-117, a novel inhibitory monoclonal antibody targeting C2, to inhibit fixation of complement was assessed. Results: iPSC-derived MNs moderately express the complement regulatory proteins CD46 and CD55 and strongly expressed CD59. Furthermore, MNs express C3aR, C5aR, and complement receptor 1. IgM anti-GM1 antibodies in serum from patients with MMN bind to MNs and induce C3 and C4 fixation on incubation with fresh serum. ARGX-117 inhibits complement activation downstream of C4 induced by patient-derived anti-GM1 antibodies bound to MNs. Discussion: Binding of IgM antibodies from patients with MMN to iPSC-derived MNs induces complement activation. By expressing complement regulatory proteins, particularly CD59, MNs are protected against complement-mediated lysis. Yet, because of expressing C3aR, the function of these cells may be affected by complement activation upstream of membrane attack complex formation. ARGX-117 inhibits complement activation upstream of C3 in this disease model for MMN and therefore represents an intervention strategy to prevent harmful effects of complement in MMN.